Device optimization for digital subthreshold logic operation - Paul, B.C.; Raychowdhury, A.; Roy, K. (IEEE transactions on electron devices, 2005)
Digital circuits operated in the subthreshold region (supply voltage less than the transistor threshold voltage) can have orders of magnitude power advantage over standard CMOS circuits for applications requiring ultralow power and medium frequency of operation. Although the implication of technology scaling on subthreshold operation is not obvious (since an obsolete technology node can deliver the same performance as a scaled technology in subthreshold), it has been shown that technology scaling helps to reduce the supply-voltage and, hence, the power consumption at iso-performance. It is possible to implement subthreshold logic circuits using the standard transistors that are designed primarily for ultra high performance super-threshold logic design. However, an Si MOSFET so optimized for performance in the super-threshold regime is not the best device to use in the subthreshold domain. We propose device designs apt for subthreshold operation. Results show that the optimized device improves the delay and power delay product (PDP) of an inverter chain by 44% and 51%, respectively, over the normal super-threshold device operated in the subthreshold region.